1979
DOI: 10.1107/s056773947900214x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous diffraction:Umweganregungpeaks in the case of a vibrating single crystal

Abstract: The positive diffraction intensity changes on forbidden (222) planes of a vibrating single crystal of Si, which are produced by simultaneous diffraction, are experimentally treated for the symmetric Laue case. The neutron diffraction experiment was performed for a flexurally vibrating as well as a non-vibrating perfect silicon bar. Several Umweganregung peaks were observed after exciting the bar into vibration while no Umweganregung peak was observed in the case of a non-vibrating crystal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…However, it is only in the case of elastically deformed perfect single crystals that very strong MBR effects, consisting of one or more double-diffraction processes, have been observed. About three decades ago, we observed that MBR effects can be strongly amplified by ultrasonic vibrations and the related intensity can be more than one order of magnitude higher than the intensity related to the allowed reflection of a perfect nondeformed crystal (Mikula et al, 1979(Mikula et al, , 1980Vrá na et al, 1981). Moreover, some possible exploitation of the MBR effects was predicted (Mikula et al, 1982).…”
Section: Introductionmentioning
confidence: 95%
“…However, it is only in the case of elastically deformed perfect single crystals that very strong MBR effects, consisting of one or more double-diffraction processes, have been observed. About three decades ago, we observed that MBR effects can be strongly amplified by ultrasonic vibrations and the related intensity can be more than one order of magnitude higher than the intensity related to the allowed reflection of a perfect nondeformed crystal (Mikula et al, 1979(Mikula et al, , 1980Vrá na et al, 1981). Moreover, some possible exploitation of the MBR effects was predicted (Mikula et al, 1982).…”
Section: Introductionmentioning
confidence: 95%
“…The Japan Society of Mechanical Engineers NII-Electronic Library Service ATEM'03, JSME-MMD, Sep. [10][11][12]2003 Next, a similar beam profile test was carried out at 2θ =34 o when using two Si slabs: one with the main face parallel to the planes (111) for symmetric reflection geometry and the other one with (11-1) planes at Ψ=22 o for strongly asymmetric transmission geometry. The obtained results are shown in Figs.…”
Section: Os04w0288mentioning
confidence: 99%
“…For X-rays, the positive umweg-diffraction peaks were first observed by Renninger [8] and Moon and Shull for neutrons in mosaic crystals [9] (many other related references can be found in the book [10]). However, it has been found that strong multiple reflection effects resulting in Umweganregung can be also in elastically deformed perfect crystals [11][12][13][14]. In the simplest case of the umweg-effect, a particular weak or forbidden primary reflection is strengthened by a successive cooperation of the two allowed reflections (secondary and tertiary).…”
Section: Multiple Reflection Umweganregung Monochromatormentioning
confidence: 99%
See 1 more Smart Citation
“…For X-rays, the positive MBR peaks were first observed by Renninger (1937). However, the situation is quite different in the case of neutron diffraction by elastically deformed perfect crystals (Mikula et al, 1979(Mikula et al, , 1982(Mikula et al, , 2006(Mikula et al, , 2012Vrá na et al, 1981). The first principal theoretical investigation in this field was performed by Ewald (1937).…”
Section: Introductionmentioning
confidence: 99%